Facile solution synthesis and characterization of CaCO3 microspheres with urchin-shaped structure - Zhang, W.; Li, Xin Yong; Qu, Z.; Zhao, Q.; Chen, G. (Elsevier BV, 2010)
Urchin-shaped CaCO3 microspheres were successfully synthesized by a facile low-temperature solution-phase method. The product was characterized with X-ray diffraction (XRD), Raman spectra and high resolution transmission electron microscopy (HRTEM). The characterization results revealed that the structure of the urchin-shaped CaCO3 was grown along the (104) crystal plane with a calcite structure. Furthermore, the valence states and the surface chemical compositions of CaCO3 were further identified by X-ray photoelectron spectroscopy (XPS). This study provides a simple method to prepare urchin-shaped CaCO3 microspheres in large scale, which broads their practical applications. © 2009 Elsevier B.V. All rights reserved.